Pengaruh penggunaan repelen masal jangka panjang pada suatu pemukiman terhadap keberadaan nyamuk Aedes aegypti (L.) (Diptera: Culicidae) - Upik Kesumawati Hadi; Singgih Harsoyo Sigit; Dwi Jayanti Gunandini; Susi Soviana; Sugiarto Sugiarto (Perhimpunan Entomologi Indonesia, 2008)
A Study of The Effect of Mass Treatment of Repellent on Aedes aegypti (L.) (Diptera: Culicidae). Larval populations was carried out during 14 week period at Laladon village Bogor. A total of 3684 respondents were treated and 202 houses were surveyed for house index (HI), container index (CI), and breteau index (BI). The results showed that long-term mass treatments were effective to decrease 64.85% of the HI, 27.15% CI and 13.57% of BI, up to three weeks after the last application of the repellent. Final checks which were done four weeks later resulted HI as low as 13.86%, CI 7.68%, and BI 3.84%, compared to those at the beginning of the survey which were 73.27%, 31.87% and 15.93%, respectively.